The Influence of Venous Characteristics on Peripherally Inserted Central Catheter-Related Symptomatic Venous Thrombosis in Cancer Patients - Wang GD; Wang HZ; Shen YF; Dong J; Wang XP; Wang II XZ; Zheng YY; Chen J; Guo SS (Cancer Management and Research, 2020)
Guo-Dong Wang, Hong-Zhi Wang, Yan-Fen Shen, Jing Dong, Xin-Peng Wang, Xiao-Zheng Wang II, Yuan-Yuan Zheng, Jie Chen, Shuang-Shuang Guo Key Laboratory of Carcinogenesis and Translational Research (Ministry of Education/Beijing), ICU, Peking University Cancer Hospital & Institute, Beijing 100142, People’s Republic of ChinaCorrespondence: Hong-Zhi Wang; Yan-Fen ShenKey Laboratory of Carcinogenesis and Translational Research (Ministry of Education/Beijing), ICU, Peking University Cancer Hospital & Institute, No. 52 Fucheng Road, Haidian District, Beijing 100142, People’s Republic of ChinaTel/Fax +86 10-88196112Email doctorwhz@163.com; shenyanfen1205@163.comBackground: With increasing use, peripherally inserted central catheters (PICCs) are associated with the risk of venous thrombosis. Few studies have focused on the relationships between venous thrombosis and venous characteristics. This study aimed to identify effects of venous characteristics on symptomatic PICC-related venous thrombosis in cancer patients and explore the relationship between venous characteristics and blood flow velocity.Methods: The data of patients who underwent placement of PICC were retrospectively studied between January 2015 and September 2017. Symptomatic PICC-related venous thrombosis was confirmed by ultrasound. Univariable, multivariable logistic regression analyses were performed to identify the risk factors associated with PICC-related venous thrombosis. In October 2017, 169 patients with PICCs were enrolled prospectively, and the relationships between blood flow velocity and venous characteristics were recorded and analyzed.Results: A total of 2933 cancer patients were enrolled in this study; of these patients, 68 experienced symptomatic venous thrombosis. In the bivariate analysis, body mass index (BMI), history of venous thrombosis, triglycerides, tumor category, vessel diameter, vessel depth and arm circumference were associated with thrombosis. The multivariable analyses showed that arm circumference, vascular diameter, triglyceride level and tumor category were independent risk factors for thrombosis. Blood flow velocity was positively correlated with vessel depth and arm circumference but not with vessel diameter.Conclusion: Different venous characteristics can lead to different blood flow rates, which can affect the incidence of thrombosis. A vein depth of greater than 1.07cm or less than 0.57cm was associated with a higher incidence of PICC-related venous thrombosis, and the greater the arm circumference and vessel diameter, the greater the risk of venous thrombosis.Keywords: peripherally inserted central catheters, cancer, venous thrombosis, risk factors, venous characteristics